Spatiotemporal psychopathology: an integrated brain-mind approach and catatonia - Northoff, Georg; Hirjak, Dusan (Schizophrenia research, 2024)
Catatonia is featured by complex symptoms combining motor, affective and behavioral phenomena as well as by its syndrome character with trans-diagnostic occurrence. It paradigmatically shows the limits of current forms of psychopathology like affective and cognitive approaches with respect to both clinical symptoms and brain mechanisms. We therefore suggest Spatiotemporal Psychopathology (STPP) which, as recently introduced, is here developed further following the latest findings in both clinical psychiatry and neuroscience. STPP is characterized by two core features: (i) an experience-based approach that accounts for symptoms primarily in terms of first-person experience of time-space as distinct from third-person observation of specific functions and related behavior; (ii) an integrated brain-mind approach where the brain's neural topography and dynamic, e.g., inner time and space, are shared by the mind's mental topography and dynamic, e.g., time-space experience, as their “common currency”. We demonstrate how these two features can well account for both symptom complexity and trans-diagnostic nature of catatonia. In conclusion, catatonia can serve as paradigmatic example for the need to develop a more comprehensive psychopathological approach in psychiatry. This is provided by STPP that allows integrating subjective experience, clinical symptoms and the brain's neural activity in terms of their inner space-time, e.g., topography and dynamic.